2018
DOI: 10.1038/s41467-017-02525-w
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution TADs reveal DNA sequences underlying genome organization in flies

Abstract: Despite an abundance of new studies about topologically associating domains (TADs), the role of genetic information in TAD formation is still not fully understood. Here we use our software, HiCExplorer (hicexplorer.readthedocs.io) to annotate >2800 high-resolution (570 bp) TAD boundaries in Drosophila melanogaster. We identify eight DNA motifs enriched at boundaries, including a motif bound by the M1BP protein, and two new boundary motifs. In contrast to mammals, the CTCF motif is only enriched on a small frac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

51
749
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 751 publications
(805 citation statements)
references
References 71 publications
51
749
2
3
Order By: Relevance
“…Whereas the lack of CTCF is embryonic lethal in mammals, in Drosophila CTCF null mutants (completely lacking both maternal and zygotic CTCF) survive past the larval stage and die as late pupae with visible defects associated with Hox gene misexpression . Although Drosophila CTCF is clearly linked to functional regulatory domains in the Hox complexes, it is generally only weakly enriched at TAD boundaries . A recent paper suggests that CTCF may have a specific role in certain differentiated cell types as this study found a stronger enrichment of CTCF at TAD borders in a cell line derived from larval central nervous system than in Kc167 cells originally derived from embryos .…”
Section: How Is Domain Architecture Established Across Different Orgamentioning
confidence: 50%
See 4 more Smart Citations
“…Whereas the lack of CTCF is embryonic lethal in mammals, in Drosophila CTCF null mutants (completely lacking both maternal and zygotic CTCF) survive past the larval stage and die as late pupae with visible defects associated with Hox gene misexpression . Although Drosophila CTCF is clearly linked to functional regulatory domains in the Hox complexes, it is generally only weakly enriched at TAD boundaries . A recent paper suggests that CTCF may have a specific role in certain differentiated cell types as this study found a stronger enrichment of CTCF at TAD borders in a cell line derived from larval central nervous system than in Kc167 cells originally derived from embryos .…”
Section: How Is Domain Architecture Established Across Different Orgamentioning
confidence: 50%
“…A recent paper suggests that CTCF may have a specific role in certain differentiated cell types as this study found a stronger enrichment of CTCF at TAD borders in a cell line derived from larval central nervous system than in Kc167 cells originally derived from embryos . In addition to CTCF, Drosophila contains a number of less‐conserved insulator binding proteins, such as Chromator and boundary element associated factor of 32 kD (BEAF‐32), that are much more highly enriched at TAD boundaries and appear to serve a more general architectural function …”
Section: How Is Domain Architecture Established Across Different Orgamentioning
confidence: 63%
See 3 more Smart Citations